Palm weevil larvae (Rhynchophorus phoenicis Fabricius) and orange-fleshed sweet potato-enriched biscuits improved nutritional status in female Wistar albino rats - Ayensu, Jessica; Larbie, Christopher; Annan, Reginald Adjetey; Lutterodt, Herman; Edusei, Anthony; Su, Peng Loh; Asiamah, Ernest Amponsah (Hindawi, 2020)
Edible insects have emerged as an inexpensive alternative source of protein for reducing the burden of malnutrition worldwide. However, there is a dearth of evidence on its efficacy, and thus, the aim of this study was to investigate the effect of edible insect consumption on the nutritional status of female Wistar albino rats. The study assessed the subchronic effect of palm weevil larvae (PWL) and orange-fleshed sweet potato- (OFSP-) enriched biscuits (fortified biscuits (FB), plain biscuits (PB), biscuits fortified with PWL (PWB), and biscuits fortified with OFSP only (SPB)) as a model to predict the potential of PWL to improve the nutritional status of pregnant women in Ghana. Twenty-five female Wistar albino rats were randomly assigned to five experimental groups to receive one of the five feed supplements for 28 days. After which, the effects of treatment on haematological and biochemical parameters including lipid profile were assessed. No significant differences were observed with haematological (Hb) parameters. However, total cholesterol levels of the FB, PB, PWB, and SPB were significantly higher than in the N group. Apart from elevated total cholesterol concentrations, biscuits fortified with PWL had no adverse effects and can be a nutritious snack for maintaining acceptable HB levels.